Clean Future: Design of an efficient and feasible water treatment plant for rural South-Bengal - Avijit Mallik; Md. Arman Arefin (Diponegoro University, 2019)
Waste water treatment is an important issue because of lessening water resources. The primary reason for waste water treatment process is to expel the different constituents of the polluting load: solids, natural carbon, supplements, inorganic salts, metals, pathogens and so on. In this paper, mainly de-centralized method is considered as a solution. A new rural wastewater treatment process is introduced with proper planning and designing by using empirical equations. This paper exhibits the waste water treatment technologies present in Bangladesh, to expel contaminants from wastewater, for example, halogenated hydrocarbon mixes, overwhelming metals, colors, pesticides, and herbicides, which speak to the fundamental toxins in waste water. This research shows that the proposed decentralized system is more feasible economically and environmentally (about 75% BOD removal), since the centralized system needs modern machineries and high initial investment. To design a sustainable wastewater treatment system for developing area, further assessment on environmental, health, social and institutional aspects are recommended.